Facile synthesis of polyethylene-modified asphalt by chain end-functionalization. (February 2022) - Li, Mengru; Chen, Xi; Cong, Peiliang; Luo, Chunjia; Zhu, Liuyu; Li, Huayi; Zhang, Yanmei; Chao, Min; Yan, Luke
Abstract: Polyethylene (PE) is an inexpensive asphalt additive, the application of which provides a cost-effective way to improve the performance of asphalt pavements. However, the poor storage stability of PE-modified asphalt limits its large-scale application. The effective synthesis of stable PE-modified asphalt remains challenging. Here, we report the synthesis of storage-stable PE-modified asphalt using end-group functionalized PE. The low molecular weight NH2 -terminated-PE (NPE) was synthesized and dispersed into asphalt, as confirmed by fluorescence microscopy. After 48 h in an oven at 163 °C, the modified asphalt sampled from top and bottom showed similar softening points, demonstrating great storage stability. Specifically, the difference of softening points is 1.1 °C and 0.4 °C for asphalt with 3 wt% and 5 wt% NPE addition, which exceeded most PE-modified asphalt in previous reports. The addition of NPE to asphalt also reduced the penetration and increased the low temperature ductility. Improved rheology of NPE-modified asphalt was illustrated by dynamic shear rheometer and stress creep recovery test. Our work has demonstrated that storage stability of PE-modified asphalt successfully enhanced by end-group functionalization of PE. With good storage stability, the NPE-modified asphalt would have potential application as pavements. Graphical abstract: Image 1 Highlights: An NH2 -terminated-PE (NPE) was synthesized for asphalt modification. NPE modified asphalt has storage stability that exceeds most previously reported. NPE improve service performance of matrix asphalt.